The trouts of the upper Kura and Aras rivers in Turkey, with description of three new species (Teleostei: Salmonidae) - Turan, Davut; Kottelat, Maurice; Kaya, Cüneyt (Zootaxa, 2022)
The taxonomic status of the resident and anadromous trout species native to the Kura and Aras river drainages is evaluated, and three resident species are recognised in the upper reaches of Kura and Aras drainages in Turkey. Salmo murathani, new species, is described from slow flowing tributaries of the Aras River. It is distinguished by the general body color dark greyish in life; the numerous black spots on body, present on the back and on the middle and upper parts of the flank, and on the anterior part of the lower flank in males and females larger than about 230 mm SL; the number of black spots increases with size, in both males and females; and various meristic and morphometric characters. Salmo araxensis, new species, is described from fast flowing tributaries of the Aras River. It is distinguished by the general body color greyish to brownish in life; only few black spots on the body, restricted to the back and the upper part of the flank, their number not increasing with size in both sexes; and various meristic and morphometric characters. Salmo ardahanensis, new species, is described from head waters of the Kura River. It is distinguished by the general body color dark brownish in life; the roundish black spots on the body, scattered on the back, and the middle and upper parts of the flank in most specimens, rarely restricted to the back and the upper part of the flank; in females, the black spots are few, restricted to the back and the upper part of the flank; the number of black spots increases slightly with size in males; the adipose fin is large, almost reaching to caudal-fin base in males larger than about 170 mm SL; and various meristic and morphometric characters.